FORMER SOVIET AUTHORITIES’ POLICY OF RELOCATING POPULATION IN UZBEKISTAN DURING 1925-1935 - Amirdinov Jahongir Abdumajidovich (American Journals Publishing, 2023)
One of the greatest tragedies of the 20th century was the policy of collectivization of agriculture by the former Soviet authorities. The result of Stalin's prescribed and deformed collectivization was unprecedented repression. Collectivization and the "extermination of the Kulaks as a class" led to the forced deportation of almost two million peasants to the remote northern and sparsely populated areas of the country, the deaths of hundreds of thousands of people, and ultimately the destruction of agriculture. The policy of collectivization in 1932 and 1933 resulted in a devastating famine that killed millions of peasants and led to a new wave of rural repression.